2010
DOI: 10.1007/s12098-010-0248-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vasoactive Intestinal Peptide in Hyperoxia-Induced Injury of Primary Type II Alveolar Epithelial Cells

Abstract: VIP exerts a protective role in the hyperoxia-induced oxidative stress damage in AECIIs, which probably attributed to its anti-oxidant and anti-apoptosis property.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Since the inflammatory cells appear in the first few hours of hyperoxia exposure [ 43 ], early inhibition of the inflammatory response might prevent the lung injury and thus, this pathway is expected to contribute to the development of BHR. As confirmed by our findings (Figure 3 A, B), VIP was shown to protect alveolar epithelial cells against hyperoxia via decreasing neutrophil influx into the lung [ 27 , 44 ]. Thus, treatments with sildenafil or VIP protect against the deleterious consequences of hyperoxia-induced lung inflammation by inhibiting polymorphonuclear cell infiltration into the alveolar compartment and reducing the consecutive tissue destruction.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Since the inflammatory cells appear in the first few hours of hyperoxia exposure [ 43 ], early inhibition of the inflammatory response might prevent the lung injury and thus, this pathway is expected to contribute to the development of BHR. As confirmed by our findings (Figure 3 A, B), VIP was shown to protect alveolar epithelial cells against hyperoxia via decreasing neutrophil influx into the lung [ 27 , 44 ]. Thus, treatments with sildenafil or VIP protect against the deleterious consequences of hyperoxia-induced lung inflammation by inhibiting polymorphonuclear cell infiltration into the alveolar compartment and reducing the consecutive tissue destruction.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, enhancing NO production in the lungs may counteract the elevated smooth muscle tone via a direct effect [ 23 ] or prevent against the development of chronic lung inflammation and subsequent airway remodeling [ 24 ]. Similar to NO, vasoactive intestinal peptide (VIP), which is also an inhibitory relaxant mediator of the non-adrenergic, non-cholinergic nervous pathway, may also exhibit dual bronchodilatory and anti-inflammatory potential [ 25 27 ]. Thus, we aimed at investigating whether the restoration of the NO-dependent processes with a phosphodiesterase type 5 (PDE5) inhibitor, such as sildenafil, or with VIP provides an effective protection against the development of BHR in the acute phase of hyperoxia.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some studies have suggested that the survival and apoptosis of AECII cells may be involved in the pathological changes of hyperoxiainduced ALI and BPD, which determines the outcome of repair following lung injury (25,26). Previous studies have also found that the excessive apoptosis of AECII cells aggravated pulmonary pathological alteration, which may induce an inflammatory reaction and may aggravate the injury to residual lung tissue (23,(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%